A Novel Negative Regulator of Adipogenesis: MicroRNA‐363. (13th January 2014) - Chen, Lin; Cui, Junhui; Hou, Jia; Long, Jie; Li, Cai; Liu, Lei
Abstract : The differentiation of adipose tissue‐derived stromal cells (ADSCs) into adipocytes involves a highly orchestrated series of events that includes cell lineage commitment, mitotic clonal expansion, growth arrest, and terminal differentiation. However, the molecular mechanisms controlling adipogenesis are not yet completely understood. In this study, we investigated whether microRNAs (miRNAs) play a role in adipocyte differentiation. Microarray analysis was performed to determine the miRNA expression profile during ADSC differentiation, and miR‐363 was found to be one of the most significantly downregulated miRNAs. We show that the overexpression of miR‐363 in ADSCs inhibited mitotic clonal expansion and terminal differentiation. Furthermore, ectopic introduction of miR‐363 into ADSCs markedly reduced the levels of E2F3, a key transcription factor that regulates growth and proliferation during mitotic clonal expansion. Finally, using an EGFP/RFP reporter assay, we demonstrate that miR‐363 can directly target the 3′UTR of E2F3 . Taken together, these results suggest that miR‐363 regulates the transition from mitotic clonal expansion to terminal differentiation during adipogenesis in ADSCs, at least in part, by targeting E2F3 . Stem Cells   2014;32:510–520